2023
DOI: 10.1111/jnc.16005
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells‐based disease modeling, drug screening, clinical trials, and reverse translational research for amyotrophic lateral sclerosis

Hideyuki Okano,
Satoru Morimoto,
Chris Kato
et al.

Abstract: It has been more than 10 years since the hopes for disease modeling and drug discovery using induced pluripotent stem cell (iPSC) technology boomed. Recently, clinical trials have been conducted with drugs identified using this technology, and some promising results have been reported. For amyotrophic lateral sclerosis (ALS), a devastating neurodegenerative disease, several groups have identified candidate drugs, ezogabine (retigabine), bosutinib, and ropinirole, using iPSCs‐based drug discovery, and clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…There has recently been renewed efforts in the development of therapeutics for ALS [ 216 ] invoking the potential role of mitochondria [ 217 ] and the gut–brain axis [ 218 ], as well as anti-sense therapies [ 219 ] and personalized immunotherapy [ 220 ]. Future efforts to better understand the pathogenesis of ALS and screen for effective treatments will use human organoids composed of iPSC [ 221 , 222 ] discussed in the last section.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…There has recently been renewed efforts in the development of therapeutics for ALS [ 216 ] invoking the potential role of mitochondria [ 217 ] and the gut–brain axis [ 218 ], as well as anti-sense therapies [ 219 ] and personalized immunotherapy [ 220 ]. Future efforts to better understand the pathogenesis of ALS and screen for effective treatments will use human organoids composed of iPSC [ 221 , 222 ] discussed in the last section.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…We have recently established the method called extended endothelial cell culture method (EECM) for differentiating BMEC-like cells from human induced pluripotent stem cells (hiPSCs) and investigated the role of the BBB in pathological conditions(Nishihara et al, 2020; Nishihara et al, 2021; Matsuo et al, 2023). Previous studies and reviews reported that hiPSC models reflect human disease pathophysiology, therapeutic effect, and clinical condition of patients (Okano et al, 2020; Okano and Morimoto, 2022; Morimoto et al, 2023; Okano et al, 2023). Widely used differentiation methods for BMEC-like cells(Lippmann et al, 2012; Qian et al, 2017) show a robust diffusion barrier and expression of several BMEC-specific transporters but have some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…To bridge the gap, in vitro models have been developed as recently reviewed (Zhou et al, 2023). Human induced pluripotent stem cells (hiPSC) can be exploited for a deeper understanding of developmental biology, disease modeling, and testing of drugs or therapeutic efficiency (Okano et al, 2023) and are therefore valuable tools for addressing ALS pathogenesis. Pioneered by Takahashi and Yamanaka (Takahashi and Yamanaka, 2006), iPSC technology has experienced rapid development, eliciting hiPSC determination towards various lineages.…”
Section: Introductionmentioning
confidence: 99%